Productive-prosociality, tensions of a solidarity-based entrepreneurial subjectivity: A study with Peruvian social entrepreneurs - Angela Vera Ruiz; Pontificia Universidad Católica del Perú; Agustín Espinosa; Pontificia Universidad Católica del Perú (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2020)
In recent decades, the study of entrepreneurship has been strengthened and extended from an approach that challenges the need to raise awareness of its social contribution. This study seeks to understand how the coexistence of discourses on the creation of social value and economic value are integrated into entrepreneurial subjectivity. After interviewing 26 Peruvian social entrepreneurs, a new concept, with psychosocial aspects, was proposed. This concept is an apparent paradox that integrates social and economic goals. For that reason, it has been called productive-prosociality, considering theoretical developments on prosociality and sustainability in the field of entrepreneurship studies. The apparent oxymoron quality of the concept is analysed in three discursive repertoires that give it content. A possible subjective repositioning in the figure of some new entrepreneurs in the convulsed present times, is discussed. The results raise the possibility of undertaking a venture from a position of solidarity that transcends the individualistic and competitive aims of the current capitalist model.